Endoscopic resection of Barrett's adenocarcinoma: Intramucosal and low‐risk tumours are not associated with lymph node metastases. Issue 3 (15th March 2021) - Benech, Nicolas; O'Brien, Jean Marc; Barret, Maximilien; Jacques, Jéremie; Rahmi, Gabriel; Perrod, Guillaume; Hervieu, Valérie; Jaouen, Alexandre; Charissoux, Aurélie; Guillaud, Olivier; Legros, Romain; Walter, Thomas; et al.
Abstract: Background: Superficial oesophageal adenocarcinoma can be resected endoscopically, but data to define a curative endoscopic resection are scarce. Objective: Our study aimed to assess the risk of lymph node metastasis depending on the depth of invasion and histological features of oesophageal adenocarcinoma. Methods: We retrospectively included all patients undergoing an endoscopic resection for T1 oesophageal adenocarcinoma among seven expert centres in France in 2004–2016. Mural invasion was defined as either intramucosal or submucosal tumours; the latter were further divided into superficial submucosal (<1000 mm) and deep submucosal (>1000 mm). Absence or presence of lymphovascular invasion and/or poorly differentiated cancer (G3) defined a low‐risk or a high‐risk tumour, respectively. For submucosal tumours, invasion depth and histological features were systematically confirmed after a second dedicated histological assessment (new 2‐mm thick slices) performed by a second pathologist. Occurrence of lymph node metastasis was recorded during the follow‐up from histological or PET CT reports when an invasive procedure was not possible. Results: In total, 188 superficial oesophageal adenocarcinomas were included with a median follow‐up of 34 months. No lymph node metastases occurred for intramucosal oesophageal adenocarcinomas ( n = 135) even with high‐risk histological features. Among submucosal oesophageal adenocarcinomas, only tumours with lymphovascular invasion or poorly differentiated cancer or with a depth of invasion >1000 μm developed lymph node metastasis tumours ( n = 10/53%; 18.9%; hazard ratio 12.04). No metastatic evolution occurred under a 1000‐mm threshold for all low‐risk tumours (0/25), nor under 1200 mm (0/1) and three over this threshold (3/13%, 23.1%). Conclusion: Intramucosal and low‐risk tumours with shallow submucosal invasion up to 1200 mm were not associated with lymph node metastasis during follow‐up. In case of high‐risk features and/or deep submucosal invasion, endoscopic resections are not sufficient to eliminate the risk of lymph node metastasis, and surgical oesophagectomy should be carried out. These results must be confirmed by larger prospective series. Key Summary: Superficial oesophageal adenocarcinoma (OAC) can be resected endoscopically. Data to define a curative endoscopic resection with a low lymph node metastasis (LNM) risk are scarce especially for tumours invading the submucosa. Curative endoscopic resections have been reported in selected OAC invading the first 500 mm of the submucosa, but surgical series showed an LNM risk ranging from 0% to 50%, making endoscopic resection a questionable curative treatment. High‐risk histological features were not associated with LNM in intramucosal tumours. LNM occurred only for tumours invading the submucosa with a depth ≥1200 mm or with high‐risk histological features regardless of the depth of invasion. Endoscopic resection may be a valid and curative therapeutic option for all intramucosal tumours and for submucosal oesophageal adenocarcinoma with an invasion depth ≤1000 mm and low‐risk histological features.